The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s00702-019-02084-y
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of major depression: drawbacks and challenges

Abstract: Major depression is a leading contributor to the global burden of disease. This situation is mainly related to the chronicity and/or recurrence of the disorder, and to poor response to antidepressant therapy. Progress in this area requires valid animal models. Current models are based either on manipulating the environment to which rodents are exposed (during the developmental period or adulthood) or biological underpinnings (i.e. gene deletion or overexpression of candidate genes, targeted lesions of brain ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
261
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(270 citation statements)
references
References 276 publications
(313 reference statements)
6
261
0
3
Order By: Relevance
“…In the novelty supressed feeding test, aged mice were quicker to consume food in a novel environment suggested lower novelty-induced hyponeophagia. These findings are consistent with reduced anxiety and opposite to the effects seen in rodent models of depression where increased feeding latencies are consistently observed (Planchez et al, 2019). In contrast, aged animals had reduced reward sensitivity in the SPT.…”
Section: Aged Mice Exhibit Emotional Bluntingsupporting
confidence: 82%
See 1 more Smart Citation
“…In the novelty supressed feeding test, aged mice were quicker to consume food in a novel environment suggested lower novelty-induced hyponeophagia. These findings are consistent with reduced anxiety and opposite to the effects seen in rodent models of depression where increased feeding latencies are consistently observed (Planchez et al, 2019). In contrast, aged animals had reduced reward sensitivity in the SPT.…”
Section: Aged Mice Exhibit Emotional Bluntingsupporting
confidence: 82%
“…Using a series of different measures of stress reactivity and affective behaviour we also found evidence of a blunted emotional response in aged mice. It is interesting to observe that the effects were not typical of that seen in models of depression (Planchez et al, 2019). In assays used to measure anxiety and depression-related behaviours we found effects suggesting lower levels of anxiety but reduced reward sensitivity.…”
Section: Discussionmentioning
confidence: 80%
“…No differences were observed across groups in the total number of immobility episodes ( Figure 2E; F1,25= 2.91, P=0.1006 for PS effect; F1,25= 0.91, P=0.3487 for CF effect). We used the sucrose preference test (SPT) to evaluate anhedonia, a symptom often seen in depression (Planchez et al, 2019). A significant PS x CF interaction was observed on the preference for 4% sucrose solution ( Figure 2F; F1,26.9= 3.24, p=0.0416).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, it was identified that at 3-week post-ovariectomy appears anxietylike behavior, but from 6-week post-ovariectomy in addition to anxiety-like behavior, also increases depression-like behavior in rats, supporting an experimental model of surgical post-menopause [25] measured by scoring ambulation, rearing or nose approaching to an object; sexual behavior can be measured by conditioned place preference, number of mounts, latency and number of ejaculations. All these behaviors are normally studied under controlled environments that are designed specifically to the required behavioral display and every feature of the environment; the experimental subjects or chemical agents with probed effects on humans have been studied in this environment with the purpose of establishing these manipulations as models of a specific behavior (see Table 2) as spatial learning and memory, or models of specific pathologies behaviorally expressed as is the case of anxiety [28], depression [29], obsessive compulsive disorder [30], Parkinson [31], epilepsy [32] or addictive behaviors [33], and sleep deprivation [34], among others.…”
Section: Measuring Behaviormentioning
confidence: 99%